Evolutionary game analysis of multi-stakeholders in the WEEE recycling industry under propaganda subsidies and environmental damage taxes - Wang, Jian (Waste management (New York, N.Y.), 2024)
Copyright © 2024 Elsevier Ltd. All rights reserved.